Utility of endoscopic anatomical optical coherence tomography in functional rhinoplasty - Balakrishnan, Santosh (J Biomed Opt, 2020)
Objective measurement of the nasal valve region is valuable for the assessment of functional rhinoplasty surgical outcomes. Anatomical optical coherence tomography (aOCT) is an imaging modality that may be used to obtain real-time, quantitative, and volumetric scans of the nasal airway. We aim to evaluate if volumetric aOCT imaging is useful for the examination of the nasal valve region before and after functional rhinoplasty procedures. aOCT scans of the nasal valves were performed on four cadaveric heads before and after spreader graft and butterfly graft procedures. The resulting aOCT images were compared against video endoscopy images, and the segmented volumes of the nasal airway obtained from aOCT scans were compared with computed tomography (CT) derived volumes acquired under the same conditions. The aOCT-derived volumes match the CT volumes closely, with a mean Dice similarity coefficient of 0.88 and a mean Hausdorff distance of 2.3 mm. Furthermore, the aOCT images were found to represent the shape of the nasal cavity accurately. Due to its ability to perform real-time, quantitative, and accurate evaluation of the nasal airway, aOCT imaging is a promising modality for the objective assessment of the nasal valves before and after functional rhinoplasty procedures.